Mitigasi Kebencanaan Sambaran Petir pada Kawasan Destinasi Pariwisata Embung Jokaton - Utama, Budi (ReTII, 2022)
ABSTRACT This paper describes the design analyses of a lightning protection system for direct lightning stroke. The design was done on the contour of the land of small hills, with the distribution of several small hills that fill the surface space of the land. The location was determined based on the discourse of the community of Sengir hamlet, Kalirejo village, Kokap sub-district, Kulon Progo – Special District of Yogyakarta during a Real Work Lecture for students of the Yogyakarta National Institute of Technology, December 2021, with a letter of the village head.of Kalirejo number: 289/2004/XII/2021. The Rolling Sphare Method was carried out at several points of the installation of the lightning on the top of the triangle tower which having four levels/stages. The Model of design of the lightning protection system at Embung-Jokaton was obtained by using an electrogeometric model. The result of the design analyses for mitigating show that the zoning of protection were formed by a conicals space that cover the surface of the Embung Jokaton with magnitude of areas were 29 865 m2. and at the same time, the six arcs of shield of the lightning stroke was formed by the six lightning rods (splitzen) that located at the top of the triangle tower as apparatus for mitigating of disaster due to the lightning stroke in outdoor.. Keyword : Mitigation, disaster, Lightning